Changes in hemlock looper [Lepidoptera: Geometridae] pupal distribution through a 3-year outbreak cycle - Hébert, C.; Jobin, L.; Berthiaume, R.; Coulombe, C.; Dupont, A. (Phytoprotection, 2001)
The hemlock looper, Lambdina fiscellaria, pupal distribution was studied through a 3-year outbreak cycle near Lac Princeton on Anticosti Island in Quebec. Over the 3 years, 10 balsam fir trees were cut and all pupae were counted on the stem and branches (non-foliated vs foliated parts) of the lower, middle and upper crowns and on the stem below crown. In pre-outbreak conditions, pupae were mostly found on branches of the middle and upper crowns. During the outbreak, pupal density did not increase on these parts of the trees, since pupae were mostly found on the stem, from the ground to the middle crown, and on branches of the lower crown. Few pupae were found on the foliated portion of branches in post-outbreak conditions but most were found on the basal non-foliated part of branches, which appears to be a preferred location for hemlock looper pupation. In order to optimize detection of population increases in monitoring networks, we suggest using pupal traps at breast height on balsam fir trees.